Jawapan

2016-09-06T15:00:33+08:00
Y = 2(3) - 3(-2) + 6(1/2)
y = 15

4 = 2(-1) -3(3) + 6t
4 = 7 + 6t
4 - 7 = 6t
-3 = 6t
-3/6 = t
-1/2 = t
2016-09-06T15:09:51+08:00
The variables you see are unknown numbers that are replaced with alphabets. They are manipulative and can be any number in an algebraic expression.

However, in an equation, the unknowns' value(s) are fixed. When the value of an unknown in an equation changes, the other unknowns will be affected, their values change as well. 

Now let's proceed to the calculation :

y = 2r - 3s + 6t

(A) Given that
r = 3
s = -2
t = (1/2)

★ You just have to subtitute the values of the unknowns into the equation. In short, replace the unknowns with the values given.

y = 2(3) - 3(-2) + 6(1/2)
y = 6 + 6 + 3
y = 15

(B) Given that 
y = 4
s = 3 
r = -1

Subtitute the values,

(4) = 2(-1) - 3(3) + 6t
4 = -2 -9 +6t
4 = -11 + 6t
4 + 11 = 6t
15 = 6t
t = 15/6
1 5 1
tqvm
Your welcome
My pleasure to help ;)